ACNE SCARS IN INDIAN PATIENTS: PREVALENCE AND IMPACT ON QUALITY OF LIFE - Parag Gopal Kalyani (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: More than 80% of adolescents and young adults suffer from acne, which is a widespread chronic inflammatory skin disorder and one of the top 10 most common diseases in the world. Since scars can last and are frequently experienced by most people with acne, scarring can be a significant worry for acne patients. The majority of published reports on the effects of acne scars on patients’ wellbeing only employ instruments that are insufficiently sensitive and specific to evaluate the effects of scars. Additionally, despite the mismatch between a patient’s opinion of scar severity and a dermatologist’s evaluation, these investigations record scars in accordance with clinical judgment. Material and methods: This study included a total of 120 acne vulgaris participants. Dermatologists analyzed acne and scarring. Following information was gathered from medical records: Using the Dermatology Life Quality Index (DLQI), analysis of the age at acne onset, age at the time of initial care, sex, and the effect of acne scarring on QOL was done. Symptoms, feelings, leisure, work/school, interpersonal interactions, and treatment are among the ten topics covered by the DLQI. Result: For all the patients, the age at the onset of acne, age at the time of initial treatment were 16.9 ± 1.89, and 18.7 ± 1.43 years, respectively. For acne severity, 26.67% of the patients had mild acne, 46.67 % moderate acne, 22.5% severe acne and 4.17% very severe acne. Conclusion: This study’s result emphasizes the major influence scars have on quality of life, which increases with scar severity, as well as their high occurrence in acne patients. Therefore, when choosing a course of treatment, the influence of acne scars on quality of life must be taken into account. Keywords: Acne scar, Prevalence, Skin condition, Mini scars and Atrophic scars